2018
DOI: 10.1088/1674-1056/27/11/118703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3.7 T–24.5 T high magnetic fields on tumor-bearing mice

Abstract: Since high magnetic field (MF) intensity can improve the image quality and reduce magnetic resonance imaging (MRI) acquisition time, the field intensity of MRIs has continued to increase over the past few decades. Although MRIs in most current hospitals are 0.5 T-3 T, there are preclinical studies have been carried out using 9.4 T MRI, and engineers are also putting efforts on building MRIs with even higher MFs. However, the accompanied safety issue of high-field MRIs is an emergent question to address before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…[4][5][6] Limited by the availability of ultra-high field magnets and the compatibility of biological samples, there are very few studies about the bioeffects of ultra-high SMF above 20 T. A research reported that 3.7-24.5 T SMFs 9-hour exposure have overall good biosafety on tumor-bearing nude mice, except for some moderate liver impairment. 7 3.5-23.0 T SMF exposure for 2 hours did not show obvious harmful effects on healthy mice. 8 These data indicate that the magnetic field intensity, treatment time and mice health condition are all critical factors for the outcomes of high-field SMF treatment.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…[4][5][6] Limited by the availability of ultra-high field magnets and the compatibility of biological samples, there are very few studies about the bioeffects of ultra-high SMF above 20 T. A research reported that 3.7-24.5 T SMFs 9-hour exposure have overall good biosafety on tumor-bearing nude mice, except for some moderate liver impairment. 7 3.5-23.0 T SMF exposure for 2 hours did not show obvious harmful effects on healthy mice. 8 These data indicate that the magnetic field intensity, treatment time and mice health condition are all critical factors for the outcomes of high-field SMF treatment.…”
mentioning
confidence: 77%
“…To date, most safety studies of the biological effects of high field SMFs focused on 9–20 T, and have shown that high SMFs in this range did not exert deleterious effects 4–6 . Limited by the availability of ultra‐high field magnets and the compatibility of biological samples, there are very few studies about the bioeffects of ultra‐high SMF above 20 T. A research reported that 3.7–24.5 T SMFs 9‐hour exposure have overall good biosafety on tumor‐bearing nude mice, except for some moderate liver impairment 7 . 3.5–23.0 T SMF exposure for 2 hours did not show obvious harmful effects on healthy mice 8 .…”
mentioning
confidence: 99%
“…11 Tian et al per-formed a pilot study to test the effects of 9 h of 3.7-24.5 T treatment on GIST-T1 tumor-bearing nude mice, which showed overall good safety on most indicators but with moderate live damage. 12 In a separate study, they found that exposure to 3.5-23.0 T high SMFs for 2 h was relatively safe for healthy adult C57BL/6 mice. 13 An ultra-high magnet providing SMFs up to 33.0 T is now available, 14 which has been used in physics experiment 15,16 ; ; however, the biosafety of SMFs above 30.0 T is currently unknown.…”
Section: Introductionmentioning
confidence: 95%
“…Wang et al reported that exposure to 2–12 T SMFs for continuous 28 days did not generate significant adverse effects on healthy C57BL/6 mice 11 . Tian et al performed a pilot study to test the effects of 9 h of 3.7–24.5 T treatment on GIST‐T1 tumor‐bearing nude mice, which showed overall good safety on most indicators but with moderate live damage 12 . In a separate study, they found that exposure to 3.5–23.0 T high SMFs for 2 h was relatively safe for healthy adult C57BL/6 mice 13 …”
Section: Introductionmentioning
confidence: 99%
“…SMF is a safe physical method, even for strong SMFs that are ~10 times higher than the moderate SMFs we used in this study [ 37 40 ]. Here, we have also shown that exposure of ovarian cancer-bearing mice to 0.1 T~0.5 T moderate SMFs for 420 hours does not have any safety issues.…”
Section: Discussionmentioning
confidence: 99%